RESOLUSI KONFLIK KEAGAMAAN DI ACEH SINGKIL DALAM PERSPEKTIF BUDAYA DOMINAN - Haidlor Ali Ahmad (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2016)
This research article describes a conflict resolution in Aceh Singkil conducted for 10 days in February 2016. Data include previous conflicts happening both in May 2012 and October 2015. This research adopts qualitative approach with study case method. Data collection includes interview, participant observation and document analysis. The aim of this research is to identify the root of conflict by ways of exploring the local culture, the relationship between Muslims and Christians, the clash of culture and interests as well as conflict chronology. Furthermore, the author proposed a conflict resolution through ‘dominant culture’ approach adapted in Bali as a model.